Turnitin - Professional Doctor Mistakes And Verdicts Judge: Dilemma In Medical Services In Indonesia - Triono Eddy (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
The complexity of medical malpractice problems and the challenges faced when proving the cases has resulted in a backlog of cases in the court systems and tribunals set up by regulatory and professional bodies. The objectives of the research are to demonstrate how the errors and mistakes committed by healthcare practitioners create a dilemma in the Indonesia medical services sector. The current study entailed identifying, collecting, summarizing, and synthesizing existing research data related to the topic being investigated. This study entailed generating data or collecting data from the field; secondary research consists in identifying various reliable sources that may be used to develop answers to a formulated question or test a particular hypothesis. The issue of medical malpractice is a problem within the Indonesian legal system. Patients expect doctors to offer services that will improve their health and wellbeing. Furthermore, doctors should interact with patients in a professional way and provide safe and quality services. Indonesian courts use criminal law to address the problems related to medical malpractice. Even though the trend has helped in ensuring that doctors are held culpable for their acts, it has also resulted in fear among physicians. There is a need to streamline the regulation of medical practice through enactment of policies that will not hinder practitioners from performing their duties.